Enhancing Artistic and Creative Development in Early Childhood through Loose Parts Play - Kaenah, Kenah; Utami, Sri Yulia; Muawwanah, Uyu; Som, Rit (CV Berkah Syahdin Trust, 2025)
Purpose – This study aims to explore the use of loose parts play as a medium to enhance creativity and artistic expression in early childhood. It focuses on how age-appropriate arrangement of loose part materials can foster children's imagination, engagement, and enjoyment in learning activities.Design/methods/approach – This research adopts a qualitative descriptive method involving observations and documentation of early childhood learning activities that integrate loose part media. The study was conducted on a group of early childhood learners to observe how their responses and creative outputs were influenced by the use of open-ended, non-structured materials during play.Findings – The results indicate that learning through loose parts significantly increases children’s enthusiasm and curiosity, transforming learning experiences from monotonous routines into engaging and imaginative explorations. The children showed improved creative thinking, imagination, and ease in understanding concepts through interactive and free-form learning activities.Research implications/Limitations – The study was limited to observation-based analysis without extended experimental measurement of long-term creative development. Further research is recommended to examine the impact of loose part media on specific domains of creativity and cognitive skills in early learners using more systematic assessments.Originality/value – This study contributes to the field of early childhood education by presenting loose part play as an innovative, flexible, and child-centered learning medium that enhances creativity and engagement. It offers practical insights for educators seeking to replace conventional, less stimulating materials with more dynamic and exploratory tools.